Wind-tunnel investigation of plume dispersion and transport over complex terrain for Colstrip Power Plant: stable stratification - Cermak, J. E., author; Petersen, Ronald L., author; Fluid Mechanics and Wind Engineering Program, Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1979)
A wind tunnel test over a 1:5000 scale model of the terrain in the vicinity of the Colstrip Power Plant, Rosebud County, Montana was performed. The tests were conducted under stable stratification and a tracer gas was released at two effective plume altitudes (381 and 476 m prototype) approximately 5.2 m (26 km prototype) upwind of Badger and Garfield Peaks. The resulting ground level concentration patterns were measured to assess the validity of the EPA Valley Model assumption of plume impaction on elevated terrain. The results of the study showed the Valey Model overpredicts ground level concentrations at Badger and Garfield Peaks by a factor ranging from 1.7 to 98.0 for the wind tunnel tests corresponding to Pasquill Gifford Stability Category E. Comparison of the Plume Dispersion Characteristics with the Pasquill Gifford Curves showed that the horizontal plume spread (σ y) was one category more stable then the vertical plume spread (σ z ) and both dispersion parameters were indicative of a stable plume.
CER78-79RLP-JEC39.
Prepared for Montana Power Company.
February 1979.
Keywords: Wind tunnel models; Coal-fired power plants -- Environmental aspects -- Montana -- Rosebud County; Air -- Pollution -- Montana -- Rosebud County